(untitled) (Journal of Philosophy Culture and Political Science, 2018)
Modern communication capabilities enhance the process of interpenetration of cultures, enhancing the development of intercultural communication. Development of communication facilitates to spiritual and cultural unification of humanity. Fears of this kind require careful analysis and study of intercultural communication as one of the phenomena of global society. Authors explore modern problems of intercultural communication like categoric instruments, interdisciplinary approach, applied character and definitional crisis containing key terms disbalance like culture and communication. Key words: culture, communication, global society, information, individual.